Pengaruh Perputaran Modal Kerja, Perputaran Total Aktiva Dan Rasio Lancar Terhadap Profitabilitas Perusahaan Farmasi - Hariyanti, Tiwuk Puji; Marlena; Agustin, Weni (Jurnal Penelitian Teori & Terapan Akuntansi (PETA), 2023)
The role of the capital market in a country is as a facility for interaction between stock buyers and stock sellers to measure the efficiency of a company's operations. The company's ability to generate profits is seen from its level of profitability. Company management is required to be able to improve performance in all fields and manage owned resources effectively and efficiently to increase company profitability. One of the analytical tools in measuring the effectiveness of a company in generating profits is Return on Assets (ROA). The purpose of this study is to determine whether there is an influence of Working Capital Turnover, Total Asset Turnover, and Current Ratio partially or simultaneously on the Profitability of Pharmaceutical Companies listed on the Indonesia Stock Exchange. This study uses multiple regression analysis method. The data used includes secondary data on the Indonesia Stock Exchange. The sampling technique used purposive sampling method so that a sample of eight companies was obtained. The results of the classic assumption test show that there are no symptoms of classic assumption deviation. From the research, the following conclusions are obtained: Working Capital Turnover has no significant effect on Profitability, Total Asset Turnover has a significant effect on Company Profitability, Current Ratio has no significant effect on Profitability. While simultaneously Working Capital Turnover, Total Asset Turnover, and Current Ratio have a significant effect on Profitability